A study on fractional COVID‐19 disease model by using Hermite wavelets. (7th February 2021) - Kumar, Sunil; Kumar, Ranbir; Momani, Shaher; Hadid, Samir
Abstract : The preeminent target of present study is to reveal the speed characteristic of ongoing outbreak COVID‐19 due to novel coronavirus. On January 2020, the novel coronavirus infection (COVID‐19) detected in India, and the total statistic of cases continuously increased to 7 128 268 cases including 109 285 deceases to October 2020, where 860 601 cases are active in India. In this study, we use the Hermite wavelets basis in order to solve the COVID‐19 model with time‐ arbitrary Caputo derivative. The discussed framework is based upon Hermite wavelets. The operational matrix incorporated with the collocation scheme is used in order to transform arbitrary‐order problem into algebraic equations. The corrector scheme is also used for solving the COVID‐19 model for distinct value of arbitrary order. Also, authors have investigated the various behaviors of the arbitrary‐order COVID‐19 system and procured developments are matched with exiting developments by various techniques. The various illustrations of susceptible, exposed, infected, and recovered individuals are given for its behaviors at the various value of fractional order. In addition, the proposed model has been also supported by some numerical simulations and wavelet‐based results.